409. High Engagement in Social Distancing and Mask Wearing and Associations with Reduced COVID-19 Infection Among California College Students. (4th December 2021) - Walicek, Lindsey; Regan, Annette; L'Engle, Kelly; Couture, Marie-Claude
Abstract: Background: Engaging in preventive behaviors, including face mask wearing and social distancing, has been widely recommended, and in some cases mandated, to limit the spread of the COVID-19 disease. Despite wide-scale use, there is little data available on engagement of mask wearing and social distancing in college students and associated COVID-19 infection. Methods: A school-wide online survey was conducted (2021) among university students (n=2, 132) in California. Frequency of mask-wearing and social distancing (indoors or public settings) and diagnosis with COVID-19 infection were measured. Multiple logistic regression models assessed associations between i) mask-wearing and ii) social distancing and COVID-19 infection, controlling for race, age, gender, and living with people who have high-risk health conditions. Results: Fourteen percent (14.06%) reported previous COVID-19 infection. Most students reported wearing masks in public settings (77.9%) and indoors (58%). About half (49.9%) reported social distancing in public settings and 44.9% indoors. In multiple logistic regression models, wearing a mask indoors was associated with 30% lower odds of COVID-19 infection (OR= 0.70; 95% CI: 0.54, 0.91) but no statistically significant association was observed for wearing a mask outdoors (OR= 0.80; 95% CI: 0.59, 1.08). Social distancing indoors and outdoors was associated with a 34% (OR= 0.66; 95% CI: 0.50, 0.86) and 32% (OR= 0.68; 95% CI: 0.52, 0.88) decrease in the odds of infection, respectively. COVID-19 infection declined as the number of preventive behaviors a student engaged in increased. Compared to those who engaged in no preventive behavior, the odds of infection were 0.71 (95% CI: 0.46, 1.11) among students engaging in one behavior, 0.70 (95% CI: 0.46, 1.07) in two behaviors, 0.42 (95% CI: 0.25, 0.70) in three behaviors, and 0.48 (95% CI: 0.31, 0.74) among those who engaged in all four behaviors. Conclusion: Wearing face masks and social distancing were both associated with lower odds of COVID-19 infection. The more preventive behaviors students engaged in the less frequently they reported COVID-19 infection. Our findings support existing guidelines promoting mask wearing and social distancing to limit the spread of COVID-19 disease. Disclosures: All Authors : No reported disclosures